Faktor-Faktor yang Mempengaruhi Kepatuhan Berobat Penderita Hipertensi - Prihatin, Kurniati; Fatmawati, Baiq Ruli; Suprayitna, Marthilda (Sekolah Tinggi Ilmu Kesehatan YARSI Mataram, 2020)
Hypertension is a disease that requires long-term therapy, so that required patients adherence in treatment to control blood pressure and reduce the complication risk. Rate of adherence to treatment in Penimbung health care 2019 amounted to only 13% and the number of non-adherence 86%. The type of research was descriptive analytic with cross-sectional design.The population of this research were 1014 visit. Total samples taken were 84 patients was accidental sampling. Adherence to hypertension treatment was maesured using Modified Morisky Adherence Scale (MMAS). From these results it could be concluded that the factor of education level (p=0,000),long suffered from hypertension (p=0,005),the level knowledge about hypertension (p=0,000), familly suport (p=0,000),the role of the health officer (p=0,000),and motivation for treatment (p=0,000) had associated with adherence of hypertension patients in treatment.Gender,employment status,the participation of health insurance,access to health care are not associated with adherence of hypertension patients in treatment (p>0,05)